Export Market Orientation Strategy, External Environment, and Export Performance of SMEs in Malaysia - Singh, Harcharanjit; Saufi, Roselina Ahmad; Hassan, Asan Ali Golam (Prabandhan: Indian Journal of Management, 2017)
Globalization phenomena have changed the trends of business performance all over the world. As a result, many researchers embarked upon different journeys to examine the aftermath of globalization. Many past studies examined the relationship between export market orientation (EMO) and export performance from different parts of the world. Nevertheless, the importance of export market orientation on the firm's export performance is still a hot debate amongst the researchers. The research examined the relationship between export market orientation, external environment, and export performance for manufacturing small and medium enterprises (SMEs) in Malaysia. The survey was done on 779 manufacturing companies listed with the Federation of Malaysian Manufacturers (FMM) involved in the exporting activity and fit the SME criteria. Data was further analyzed using Partial Least Square (PLS) techniques. The research found that EMO had a significant influence on the export performance. However, the research could not support that the external environment moderated the relationship between the EMO and export performance.